2021
DOI: 10.3390/foods10030522
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and Immunomodulatory Potential of the Endemic French Guiana Wild Cocoa “Guiana”

Abstract: Guiana is a little-known and endemic variety of cocoa (Theobroma cacao), native to French Guiana. No data were available regarding its chemical composition and biological properties; therefore, a study was necessary, using Forastero as a reference. To exemplify biological activities of the cacao species, cocoa extracts were evaluated by antioxidant (DPPH, FRAP, ORAC) and anti-inflammatory assays. Our results showed that raw Guiana presented equivalent DPPH and FRAP activities, but a 1.3-fold higher antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…An approximative total polyphenol content (TPC) using the Folin-Ciocalteu method showed that COPs had lower TPC than COBs: 3.2 ± 0.3–56.5 ± 0.6 mg gallic acid equivalent/g of DW) [ 46 , 69 , 77 , 78 ]) vs. 9.8 ± 0.1–202.2 ± 6.5 mg GAE/g of DW [ 75 , 79 , 80 ]. Polyphenol contents may vary according to various parameters such as genotype [ 81 , 82 ], maturity [ 83 ], soil, and crop conditions (sun exposure, number of fruits on tree, soil type) [ 82 , 84 ].…”
Section: Chemical Composition Of Beans and Podsmentioning
confidence: 99%
“…An approximative total polyphenol content (TPC) using the Folin-Ciocalteu method showed that COPs had lower TPC than COBs: 3.2 ± 0.3–56.5 ± 0.6 mg gallic acid equivalent/g of DW) [ 46 , 69 , 77 , 78 ]) vs. 9.8 ± 0.1–202.2 ± 6.5 mg GAE/g of DW [ 75 , 79 , 80 ]. Polyphenol contents may vary according to various parameters such as genotype [ 81 , 82 ], maturity [ 83 ], soil, and crop conditions (sun exposure, number of fruits on tree, soil type) [ 82 , 84 ].…”
Section: Chemical Composition Of Beans and Podsmentioning
confidence: 99%
“…To determine the fraction of polyphenols in cocoa, several analytic methods are applied, such as the following: Colorimetric/Spectrophotometric (UV-Vis) methods [ 4 , 45 , 46 , 47 , 48 , 49 , 50 ]: Total polyphenol content by the Folin–Ciocalteu method Total anthocyanidins content by the analysis of pH variation Total flavonoids content by AlCl 3 method Total proanthocyanidins by Vanillin, DMACA, butanol-HCl or bovine serum albumin (BSA) methods Chromatographic methods [ 51 , 52 ]: Thin layer chromatography High performance liquid chromatography (Identification with or without mass spectrometry detector/Determination of the polymerization degree of tannin by thiolysis such as phloroglucinolysis) …”
Section: Bean Compositionmentioning
confidence: 99%
“…Colorimetric/Spectrophotometric (UV-Vis) methods [ 4 , 45 , 46 , 47 , 48 , 49 , 50 ]: Total polyphenol content by the Folin–Ciocalteu method Total anthocyanidins content by the analysis of pH variation Total flavonoids content by AlCl 3 method Total proanthocyanidins by Vanillin, DMACA, butanol-HCl or bovine serum albumin (BSA) methods …”
Section: Bean Compositionmentioning
confidence: 99%
See 2 more Smart Citations